Structural Organization of Innate Immune Factors in Gastric Mucosal Inflammation at H.pylori Infection in Children - О.Ye. Abaturov; O.M. Gerasymenko (Zaslavsky O.Yu., 2015)
The objective of the study was to examine, using factor analysis, structural changes in the state of innate immunity factors in the development of gastric mucosal (GM) inflammation in children with H.pylori infection. Methods. We used molecular genetic methods to determine the level of expression of TLR4, NLRC1/NOD1 in GM biopsy material and NF-B in peripheral blood lymphocytes, and enzyme-linked immunosorbent assay - to determine sCD14 and NT-proBNP levels in blood serum. Results. Using factor analysis, we have studied structural changes in the state of innate immunity factors in the development of GM inflammation in 128 children with exacerbations of chronic gastroduodenal diseases (CGDD): 70 (54.7 %) patients infected with H.pylori, and 58 (45.3 %) children, in whom H.pylori was not detected. There were obtained factors enabled to identify the main structural axes in the expression of innate immunity components, non-specific defense mechanisms that determine the development of local GM inflammation (P < 0.001). It is shown that GM nflammation in patients with chronic gastroduodenal diseases, not associated with H.pylori, is determined by two signaling systems, the activity of which is in inverse proportion: NLRC1/NOD1-associated and associated TLR4-cascades. While the leading mechanism of GM inflammation in children with H.pylori-associated CGDD is receptor-independent activation of transcription factor NF-κB, and receptor-dependent mechanisms are mostly determine NT-proBNP production.